2006
DOI: 10.1017/s135561770606067x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing attentional skills in children with acquired and developmental central nervous system disorders

Abstract: Attentional impairments in children occur in the context of both developmental and acquired disorders involving the central nervous system (CNS) and may have implications for ongoing development, potentially impeding cognitive, educational, and behavioral functions. Using a continuous performance paradigm (CPT), this study compared attentional profiles of children with developmental and acquired conditions impacting on the CNS: (i) attention deficit-hyperactivity disorder (ADHD: n 5 27); (ii) moderate traumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Children with ADHD have difficulty sustaining attention (Seidel and Joschko, 1990), and, over time, show increased reaction time (RT) and commit more omission errors, as in Trajectory D (Anderson et al, 2006; Brewer et al, 2001; but see Huang-Pollock and Nigg, 2003). In children with SBM, in contrast, RT does not increase over time, as in Trajectory B (Brewer et al, 2001; Swartwout et al, 2008).…”
Section: When To Assessmentioning
confidence: 99%
“…Children with ADHD have difficulty sustaining attention (Seidel and Joschko, 1990), and, over time, show increased reaction time (RT) and commit more omission errors, as in Trajectory D (Anderson et al, 2006; Brewer et al, 2001; but see Huang-Pollock and Nigg, 2003). In children with SBM, in contrast, RT does not increase over time, as in Trajectory B (Brewer et al, 2001; Swartwout et al, 2008).…”
Section: When To Assessmentioning
confidence: 99%
“…Two longitudinal studies that evaluated children with moderate/severe TBI showed that they displayed persistent significant difficulties compared with a healthy control group. The injured children had a significantly longer reaction time, fewer accurate responses [14] and higher rates and length of lapses in attention [40]. Another longitudinal study found poorer performances for children with severe TBI when compared to children with mild and moderate TBI and controls [22].…”
Section: Sustained Attention/vigilancementioning
confidence: 99%
“…Nevertheless, data support this theory and find children with ADHD repeatedly not performing as well as matched controls on neurocognitive tests of vigilance and sustained attention, such as the continuous performance task or CPT Halperin et al, 1990;Inoue et al, 1998;Seidman et al, 1998) where inattentiveness is indexed as errors of omission. Performance on such tasks appears positively correlated with ADHD symptoms (Anderson, Anderson, & Anderson, 2006;Epstein et al, 2003;Mahone, Pillion, Hoffman, Hiemenz, & Denckla, 2005;Marks et al, 2005;Nichols & Waschbusch, 2004). Correlations with behavioral measures of inattention vary and are at best moderate.…”
Section: Neuropsychological Constructs and Adhdmentioning
confidence: 99%